Fattening heifers for the summer or early fall market. - Smith, E.F.; Good, D.L.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
The purpose of this experiment is to develop a desirable system or systems of fattening heifer calves similar to the Deferred Full Feeding system for steer calves. The system developed for good quality steer calves consisted of three phases (1) producing 225 to 250 pounds of gain during the winter, which usually require the feeding of four to five pounds of grain per head daily; (2) grazing 90 days without grain; (3) full feeding 100 days in the dry lot. The results of several prior trials at this station with heifer calves were considered before planning this experiment
Keywords: Beef; Heifers; Grain; Gain